Molecular Features and Metal Ions That Influence 10-23 DNAzyme Activity - Rosenbach, Hannah; Victor, Julian; Etzkorn, Manuel; Steger, Gerhard; Riesner, Detlev; Span, Ingrid (Molecules, 2020)
Deoxyribozymes (DNAzymes) with RNA hydrolysis activity have a tremendous potential as gene suppression agents for therapeutic applications. The most extensively studied representative is the 10-23 DNAzyme consisting of a catalytic loop and two substrate binding arms that can be designed to bind and cleave the RNA sequence of interest. The RNA substrate is cleaved between central purine and pyrimidine nucleotides. The activity of this DNAzyme in vitro is considerably higher than in vivo, which was suggested to be related to its divalent cation dependency. Understanding the mechanism of DNAzyme catalysis is hindered by the absence of structural information. Numerous biological studies, however, provide comprehensive insights into the role of particular deoxynucleotides and functional groups in DNAzymes. Here we provide an overview of the thermodynamic properties, the impact of nucleobase modifications within the catalytic loop, and the role of different metal ions in catalysis. We point out features that will be helpful in developing novel strategies for structure determination and to understand the mechanism of the 10-23 DNAzyme. Consideration of these features will enable to develop improved strategies for structure determination and to understand the mechanism of the 10-23 DNAzyme. These insights provide the basis for improving activity in cells and pave the way for developing DNAzyme applications.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Catalysis; Deoxyribozymes (DNAzymes); Gene silencing; Metal ion cofactors; RNA hydrolysis